METODE ECONOMIC ORDER QUANTITY (EOQ) SEBAGAI ALAT KONTROL PENGENDALIAN PERSEDIAAN BAHAN BAKU KERIPIK PISANG DI UKM BANATABO - Prasetyo, Healthy Aldriany; Tambunan, Sahabat Petrus; Zulvatricia, Reakha; Siregar, Ninny Asnidar (Jurnal Inovasi Teknik Industri, 2025)
Failure to control raw material inventory will result in failure to obtain profits. Banatabo UKM's supply of raw materials for banana horns has not been optimized because it only uses predictions based on experience without carrying out economic analysis calculations which results in over stock, affecting the quality of raw materials, and causing over budget. The aim of the research is to optimize control of the supply of raw materials for horn bananas through calculating the Economic Order Quantity (EOQ) method. The research method is a quantitative method through raw material inventory data, storage and ordering costs at Banatabo UKM. The results of the research are that the optimal amount of raw material purchased using the EOQ method is 290 kg per order. Actually, Banatabo UKM purchases 101 kg of raw materials for each order. The optimal frequency of purchasing raw materials using the EOQ method is 17 times and the actual data for UKM Banatabo is 48 times. Through the EOQ method, raw material inventory costs are Rp. 974,372 every month while the actual data for UKM Banatabo is 1,568,492 every month so the savings is IDR. 594,120 or as much as 38%. Because previously UKM Banatabo had not implemented safety stock (safety inventory) and reorder points (reorder points), UKM Banatabo had to maintain a safety stock of 33 kg and a reorder point of 79 kg to facilitate the continuity of ales cycle.